Water-soluble star-comb polymer concrete viscosity reducer and preparation method thereof
A water-soluble star-comb polymer viscosity reducer with a controlled synthesis method addresses the limitations of existing reducers by providing large steric hindrance and multiple active sites, enhancing viscosity reduction and fluidity in concrete.
Patent Information
- Application Number
- CN202411234884.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Current polymer viscosity reducers for concrete lack large steric hindrance, multiple active sites, and low viscosity, leading to incomplete molecular structures and complex preparation processes that fail to meet the needs of high-grade concrete applications.
A water-soluble star-comb polymer concrete viscosity reducer is developed using a specific composition and synthesis method, incorporating polyether methoxy polyethylene glycol methacrylate, maleic anhydride, hydroxyethyl methacrylate phosphate, and catalysts like copper powder, with a controlled polymerization process to achieve a star-shaped comb structure for enhanced dispersibility and viscosity reduction.
The star-comb polymer effectively reduces concrete viscosity, improves fluidity and mechanical properties, and facilitates controllable industrial production with a simple, energy-efficient process.
Smart Images

Figure CN119119379A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to a water-soluble star-shaped and comb-shaped polymer concrete viscosity reducer and a preparation method thereof. Background Art
[0002] Polymer viscosity reducers have rich branched structures and excellent adsorption properties, which make the polymer adsorption density on the surface of cement particles high and the adsorption layer thick, which can significantly reduce the yield stress and have a lubricating effect, thereby reducing the viscosity of concrete. Therefore, adding polymer viscosity reducers is the most effective way to solve the problems of high viscosity and slow flow rate in high-grade concrete in practical applications. Concrete viscosity reducers have only a history of development of more than ten years. Whether it is molecular structure, product type, performance or viscosity reduction mechanism, they are not rich and complete enough. At present, researchers mainly focus on the preparation of comb-type viscosity-reducing polycarboxylic acid water-reducing agents through molecular structure design, but there are often problems such as single molecular structure, uncontrollable structure and complex preparation process, which cannot meet the current theoretical and application needs of concrete. Therefore, there is currently a lack of a viscosity reducer with large steric hindrance, multiple active sites and low viscosity. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a water-soluble star-comb polymer concrete viscosity reducer and a preparation method thereof to solve the current problem of lacking a polymer with large steric hindrance, multiple active sites and low viscosity.
[0004] To achieve the above-mentioned purpose, the present invention provides a water-soluble star-shaped comb-shaped polymer concrete viscosity reducer. The raw materials for preparing the water-soluble star-shaped comb-shaped polymer concrete viscosity reducer include, by mass percentage, 20-40% of monomer, 0.05-0.80% of initiator PEO-Br3, 0.01-0.20% of catalyst, 0.05-0.25% of ligand, 0.001-0.01% of deactivator, and the balance is water.
[0005] Optionally, the structure of the initiator PEO-Br3 is shown in formula (I): (I), n is 6 or 7.
[0006] Alternatively, the monomers include polyether methoxy polyethylene glycol methacrylate, maleic anhydride and hydroxyethyl methacrylate phosphate.
[0007] Optionally, the molar ratio of the polyether methoxy polyethylene glycol methacrylate, the maleic anhydride, and the hydroxyethyl methacrylate phosphate is 1:(0.5-4):(0.01-0.1).
[0008] Optionally, the molecular weight of the polyether methoxy polyethylene glycol methacrylate is 1000-3000.
[0009] Optionally, the catalyst is copper powder; and / or the ligand is tris(2-dimethylaminoethyl)amine or tris(2-aminoethyl)amine; and / or the deactivator is copper bromide.
[0010] Optionally, the chemical structural formula of the water-soluble star-comb polymer concrete viscosity reducer is as shown in formula (II): (II), Among them, n, m, b, and y are all non-zero integers.
[0011] In order to achieve the above-mentioned purpose, the present invention also proposes a preparation method of the above-mentioned water-soluble star-shaped-comb-shaped polymer concrete viscosity reducer, comprising the following steps: S1: adding polyether methoxy polyethylene glycol methacrylate, maleic anhydride, hydroxyethyl methacrylate phosphate and water into a reactor, stirring and dissolving, adding catalyst copper and copper bromide, adding ligand reaction under constant temperature and vacuum conditions, and then adding initiator to initiate polymerization reaction. After the polymerization reaction occurs, the reactor is sealed; S2: stopping the reaction after reacting for a specified time under closed conditions, removing copper powder and divalent copper complex in the reaction system, and concentrating by rotary evaporation, precipitating the concentrated liquid and vacuum drying to obtain a star-shaped-comb-shaped polymer viscosity reducer.
[0012] Optionally, the constant temperature is 20°C~50°C.
[0013] Optionally, the reaction time of adding the ligand is 10 min-30 min; and / or, the time of reacting under closed conditions until a specified time is 60 min-240 min.
[0014] The beneficial effects of the present invention are as follows: the water-soluble star-shaped and comb-shaped polymer concrete viscosity reducer provided by the present invention has a viscosity reducing polycarboxylate water reducer as an arm, and the arm contains a large number of polar groups, such as carboxyl, hydroxyl, phosphate, etc., which can be adsorbed on the surface of cement particles through electrostatic action; with a three-arm core as the center, it extends into space so that the viscosity reducing polycarboxylate water reducer is adsorbed on the surface of cement particles in a star shape; the long hydrophobic side chains and a large number of hydrophobic nuclei contained in the arms can provide a large steric hindrance for the cement particles, so that the cement particles are evenly dispersed, and a large amount of flocculated water wrapped is released, thereby reducing the viscosity, improving the fluidity and mechanical properties of the cement slurry, and the star-shaped and comb-shaped polymer viscosity reducer has a special structure and performance, large steric hindrance, many active sites, and low viscosity, thereby enhancing its viscosity reducing performance, and realizing the transformation of the molecular structure of the concrete viscosity reducer. The present invention adopts the single electron transfer living radical polymerization method (SET-LRP) which is conducive to large-scale production, has a fast polymerization rate and a high monomer conversion rate, and uses green solvent water as a reaction medium at room temperature or below (room temperature) to prepare a star-shaped-comb-shaped polymer viscosity reducer with controllable molecular weight. The polymerization process is energy-saving and environmentally friendly, and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0015] Figure 1 This is an infrared spectrum of an embodiment of the concrete viscosity reducer of the present invention; The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0017] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0018] Polymer viscosity reducers have rich branched structures and excellent adsorption properties, which make the polymer adsorption density on the surface of cement particles high and the adsorption layer thick, which can significantly reduce the yield stress and have a lubricating effect, thereby reducing the viscosity of concrete. Therefore, adding polymer viscosity reducers is the most effective way to solve the problems of high viscosity and slow flow rate in high-grade concrete in practical applications. Concrete viscosity reducers have only a history of development of more than ten years. Whether it is molecular structure, product type, performance or viscosity reduction mechanism, they are not rich and complete enough. At present, researchers mainly focus on the preparation of comb-type viscosity-reducing polycarboxylic acid water-reducing agents through molecular structure design, but there are often problems such as single molecular structure, uncontrollable structure and complex preparation process, which cannot meet the current theoretical and application needs of concrete. Therefore, there is currently a lack of a viscosity reducer with large steric hindrance, multiple active sites and low viscosity.
[0019] In order to solve the above problems, the present invention provides a water-soluble star-shaped comb-shaped polymer concrete viscosity reducer. The raw materials for preparing the water-soluble star-shaped comb-shaped polymer concrete viscosity reducer include, by mass percentage, 20-40% of monomer, 0.05-0.80% of initiator PEO-Br3, 0.01-0.20% of catalyst, 0.05-0.25% of ligand, 0.001-0.01% of deactivator, and the balance is water.
[0020] As the main component of the viscosity reducer, the monomer determines the skeleton structure of the polymer and has a decisive influence on the performance of the final product. The initiator is used to start the polymerization reaction. Its type and amount will affect the molecular weight and molecular weight distribution of the polymer. The catalyst accelerates the rate of polymerization and improves the reaction efficiency. The ligand is used to stabilize the active center of the catalyst and affect the progress of the polymerization reaction. The deactivator is used to control the accuracy of the polymerization reaction and prevent over-polymerization. Water, as a solvent and dispersion medium, helps to evenly disperse the polymer in water.
[0021] The synergistic effect of these components enables the prepared viscosity reducer to reduce the viscosity of concrete, improve its fluidity and construction performance; through molecular structure design, the interaction with cement particles is improved and the dispersion effect is enhanced; the synthesis method is controllable, which helps to achieve industrial production.
[0022] The water-soluble star-comb polymer concrete viscosity reducer of this scheme has large steric hindrance, multiple active sites and low viscosity, thereby enhancing its viscosity reducing performance and realizing the transformation of the molecular structure of the concrete viscosity reducer.
[0023] Furthermore, the structure of the initiator PEO-Br3 is shown in formula (I): (I), n is 6 or 7. Due to its special structure, the polyethylene glycol monomethyl ether side chain can participate in the polymerization reaction as an active point, which helps to form a star-shaped or comb-shaped polymer with a specific structure. The side chain structure may improve the fluidity and construction performance of concrete by improving the dispersibility of cement particles and reducing the apparent viscosity of cement-based materials. It can also give the viscosity reducer better thermal stability, allowing it to be used under a wider range of environmental conditions. Due to the spatial structure of the polyethylene glycol monomethyl ether side chain, a dense adsorption layer may be formed on the surface of cement particles, providing a significant steric hindrance effect, which helps the dispersion of cement particles, and has good water solubility, which can improve the hydrophilicity of the viscosity reducer and help its dispersion and application in aqueous systems. The initiator PEO-Br3 is homemade, and the reaction mechanism is the reaction of acyl chloride and hydroxyl groups well known in the art. It has high reaction activity, no side reactions, and is easy to carry out. According to the successful preparation of the concrete viscosity reducer polymer, it is also indirectly proved that the initiator PEO-Br3 is successfully prepared.
[0024] Furthermore, the monomers include polyether methoxy polyethylene glycol methacrylate, maleic anhydride and hydroxyethyl methacrylate phosphate.
[0025] Polyether methoxy polyethylene glycol methacrylate (MPEG-MAA) is a functional monomer of MPEG methacrylate with high esterification rate and low acid residue. It is used in the synthesis of aqueous dispersions to increase the hydrophilicity of viscosity reducers and improve their dispersibility in aqueous systems.
[0026] Maleic anhydride is an unsaturated dibasic acid that can introduce other monomers through copolymerization to increase the functionality of the polymer. In the viscosity reducer, maleic anhydride can provide unsaturated bonds, help form a polymer network with specific structure and properties, enhance the cement dispersibility of the viscosity reducer and improve its water reduction effect.
[0027] Hydroxyethyl methacrylate phosphate has a phosphate group, which can provide good water solubility and emulsification. The introduction of phosphate may enhance the interaction between the viscosity reducer and cement particles, improve its dispersion stability in cement paste, and thus reduce the viscosity of cement paste.
[0028] The combined use of these monomers can prepare a star-shaped-comb-shaped structure viscosity reducer with excellent viscosity reduction effect and high water reduction performance, which helps to improve the workability and construction performance of concrete.
[0029] Furthermore, the molar ratio of polyether methoxy polyethylene glycol methacrylate, maleic anhydride, and hydroxyethyl methacrylate phosphate is 1:(0.5-4):(0.01-0.1). By precisely controlling the polymerization reaction of these monomers, a viscosity reducer with a specific molecular structure and topological morphology can be designed to meet the specific requirements of high-performance concrete.
[0030] Further, the molecular weight of the polyether methoxy polyethylene glycol methacrylate is 1000-3000. In some embodiments, the molecular weight of the polyether methoxy polyethylene glycol methacrylate is preferably 1500-2500, more preferably 1800-2200.
[0031] Furthermore, the catalyst is copper powder; and / or the ligand is tris(2-dimethylaminoethyl)amine or tris(2-aminoethyl)amine; and / or the deactivator is copper bromide.
[0032] Catalyst copper powder can effectively reduce the activation energy of the reaction, accelerate the reaction rate, and improve the synthesis efficiency of the viscosity reducer. Tris(2-dimethylaminoethyl)amine or tris(2-aminoethyl)amine as a ligand has strong alkalinity and electron-donating ability, which can stabilize the active state of the copper catalyst and avoid its excessive reduction or oxidation during the reaction, thereby improving the stability and service life of the catalyst. In addition, this type of ligand can also adjust the molecular weight distribution and structure of the polymer by forming a stable metal-ligand complex, thereby improving the performance of the viscosity reducer. Copper bromide is used as a deactivator to control the reaction rate and improve the uniformity of the molecular weight distribution of the product. Copper bromide can be used as a deactivator in single electron transfer living radical polymerization (SET-LRP). By adjusting the concentration of active species, the polymerization reaction can be effectively controlled to achieve precise regulation of the molecular weight and molecular weight distribution of the viscosity reducer.
[0033] Furthermore, the chemical structural formula of the water-soluble star-comb polymer concrete viscosity reducer is as shown in formula (II): (II), Among them, n, m, b, and y are all non-zero integers.
[0034] The viscosity-reducing polycarboxylate water-reducing agent is used as the arm, which contains a large number of polar groups, such as carboxyl, hydroxyl, phosphate, etc. These polar groups can be adsorbed on the surface of cement particles through electrostatic action; with the three-arm core as the center, it extends into space, so that the viscosity-reducing polycarboxylate water-reducing agent is adsorbed on the surface of cement particles in a star shape; the long hydrophobic side chains and a large number of hydrophobic nuclei contained in the arms can provide a large space steric hindrance for the cement particles, so that the cement particles are evenly dispersed, releasing a large amount of flocculated water wrapped, thereby reducing the viscosity and improving the fluidity and mechanical properties of the cement slurry.
[0035] In order to solve the above problems, the present invention also proposes a method for preparing the above-mentioned water-soluble star-comb polymer concrete viscosity reducer, comprising the following steps: S1: Add polyether methoxy polyethylene glycol methacrylate, maleic anhydride, hydroxyethyl methacrylate phosphate and water into a reactor and stir to dissolve, then add catalyst copper and copper bromide, add ligand to react under constant temperature and vacuum conditions, then add initiator to initiate polymerization, and after the polymerization reaction occurs, seal the reactor; In some embodiments, unsaturated polyether methoxy polyethylene glycol methacrylate, maleic anhydride, hydroxyethyl methacrylate phosphate, and a certain amount of solvent water are added to a reactor equipped with a mechanical stirring device, and after stirring and dissolving, catalyst copper and copper bromide are added. The reaction device is placed in a constant temperature water bath, an inert gas is passed into the reactor to remove oxygen in the reaction system, a certain amount of ligand tris(2-dimethylaminoethyl)amine is added, and after reacting for a few minutes, an initiator PEO-Br3 is added to initiate a polymerization reaction, and after the polymerization reaction occurs, the reactor is quickly sealed.
[0036] S2: After the reaction is carried out under closed conditions for a specified time, the reaction is stopped, the copper powder and the divalent copper complex in the reaction system are removed, and the reaction is concentrated by rotary evaporation. The concentrated solution is precipitated and then vacuum dried to obtain a star-shaped-comb-shaped polymer viscosity reducer.
[0037] In some embodiments, the reaction is stopped after a specified time under closed conditions, the copper powder and divalent copper complex in the reaction system are removed through a neutral alumina column, and the filtrate is rotary evaporated using a rotary evaporator. Finally, the concentrated solution is precipitated with petroleum ether, and the obtained precipitate is dried under vacuum conditions to obtain a star-shaped-comb-shaped polymer viscosity reducer.
[0038] Furthermore, the constant temperature is 20°C to 50°C.
[0039] Furthermore, the reaction time of adding the ligand is 10 min-30 min; and / or, the reaction time under closed conditions until the specified time is 60 min-240 min. Reasonable control of the reaction temperature and time is conducive to controlling the reaction process and obtaining the target product.
[0040] The present invention is further described in detail below in conjunction with specific embodiments.
[0041] Embodiment 1: 40.0000g of polyether methoxy polyethylene glycol methacrylate, 5.8800g of maleic anhydride, 0.2280g of hydroxyethyl methacrylate phosphate and 138.4320g of water were weighed and put into a reaction bottle equipped with a stirring device. The reactor was placed in a constant temperature water bath (25±1°C). After stirring and dissolving, 0.03689g of copper powder and 0.0553g of copper bromide were added to the reaction bottle in sequence, and high-purity nitrogen was passed to evacuate. After 10 minutes, 0.1383g of ligand tris(2-dimethylaminoethyl)amine was removed. After 8 minutes, 0.0922g of initiator PEO-Br3 was quickly added. After reacting for 3 hours under nitrogen protection, the reaction was stopped, the copper powder and divalent copper complex in the reaction system were removed through a neutral alumina column, and the filtrate was rotary evaporated with a rotary evaporator. Finally, the concentrate was precipitated with petroleum ether, and the obtained precipitate was dried under vacuum conditions to obtain a star-comb polymer viscosity reducer.
[0042] Embodiment 2: 40.0000g of polyether methoxy polyethylene glycol methacrylate, 5.8800g of maleic anhydride, 0.2280g of hydroxyethyl methacrylate phosphate and 138.4320g of water were weighed and put into a reaction bottle equipped with a stirring device. The reactor was placed in a constant temperature water bath (35±1°C). After stirring and dissolving, 0.03689g of copper powder and 0.0553g of copper bromide were added to the reaction bottle in sequence, and high-purity nitrogen was passed to evacuate. After 10 minutes, 0.1383g of ligand tris(2-dimethylaminoethyl)amine was removed. After 8 minutes, 0.0922g of initiator PEO-Br3 was quickly added. After reacting for 3 hours under nitrogen protection, the reaction was stopped, the copper powder and divalent copper complex in the reaction system were removed through a neutral alumina column, and the filtrate was rotary evaporated with a rotary evaporator. Finally, the concentrate was precipitated with petroleum ether, and the obtained precipitate was dried under vacuum conditions to obtain a star-comb polymer viscosity reducer.
[0043] Embodiment 3: 40.0000g of polyether methoxy polyethylene glycol methacrylate, 7.8400g of maleic anhydride, 0.4560g of hydroxyethyl methacrylate phosphate and 144.8940g of water were weighed and put into a reaction bottle equipped with a stirring device. The reactor was placed in a constant temperature water bath (25±1°C). After stirring and dissolving, 0.03863g of copper powder and 0.0579g of copper bromide were added to the reaction bottle in sequence, and high-purity nitrogen was passed to evacuate. After 10 minutes, 0.1449g of ligand tris(2-dimethylaminoethyl)amine was removed. After 8 minutes, 0.0965g of initiator PEO-Br3 was quickly added. After reacting for 3 hours under nitrogen protection, the reaction was stopped, the copper powder and divalent copper complex in the reaction system were removed through a neutral alumina column, and the filtrate was rotary evaporated with a rotary evaporator. Finally, the concentrate was precipitated with petroleum ether, and the obtained precipitate was dried under vacuum conditions to obtain a star-comb polymer viscosity reducer.
[0044] Embodiment 4: 40.0000g of polyether methoxy polyethylene glycol methacrylate, 7.8400g of maleic anhydride, 0.4560g of hydroxyethyl methacrylate phosphate and 144.8940g of water were weighed and put into a reaction bottle equipped with a stirring device. The reactor was placed in a constant temperature water bath (25±1°C). After stirring and dissolving, 0.03863g of copper powder and 0.0579g of copper bromide were added to the reaction bottle in sequence, and high-purity nitrogen was passed to evacuate. After 10 minutes, 0.1449g of ligand tri(2-aminoethyl)amine was removed. After 8 minutes, 0.0965g of initiator PEO-Br3 was quickly added. After reacting for 3 hours under nitrogen protection, the reaction was stopped, the copper powder and divalent copper complex in the reaction system were removed through a neutral alumina column, and the filtrate was rotary evaporated with a rotary evaporator. Finally, the concentrate was precipitated with petroleum ether, and the obtained precipitate was dried under vacuum conditions to obtain a star-comb polymer viscosity reducer.
[0045] Comparative Example 1 In a 1000mL four-necked round-bottom flask equipped with a thermometer, an electric stirrer, an electric heating jacket, and a peristaltic pump, add 250g of water and 300g of a polyether macromonomer TPEG, the molecular weight of the TPEG used is 2400, stir and dissolve evenly, directly add a mixed solution of 3.6g of hydrogen peroxide and 16g of water, and stir for 8 minutes to fully dissolve it. Add a mixed aqueous solution consisting of 45g of acrylic acid and 60g of water and a mixed solution consisting of 1.8g of ascorbic acid, 2.3g of thioglycolic acid, and 60g of water dropwise within 2 hours and 2.5 hours, respectively, at room temperature; after the addition is completed, continue to react for 1.5 hours, add 30% sodium hydroxide solution and dilution water, and obtain a conventional polycarboxylate water reducer with a pH of 6-7 and a concentration of about 45%, and its structural formula is as follows: .
[0046] Further, infrared spectroscopy was performed on Example 1, and the results are shown in Figure 1 , at 1249 cm -1 and 526 cm -1 The stretching vibration peak of C-Br appears at 1640 cm -1 The peak of C=O stretching vibration is 2910 cm -1 The -CH2- stretching vibration peak is at 1350 cm -1 The peak of CO stretching vibration is 1249 cm -1 The peak at 3472 cm is the P=O stretching vibration peak. -1 The -OH stretching vibration peak is at 1089 cm -1 The peak at 4 is the skeleton vibration peak of quaternary carbon atoms, proving that the polymer has a star structure.
[0047] The above Examples 1 to 4 and Comparative Example 1 were tested for the flow of the pure paste according to GB / T 8077-2012 "Test Method for Homogeneity of Concrete Admixtures" and the concrete mixture performance test was tested with reference to GB / T 50080-2002 "Standard for Test Method for Performance of Ordinary Concrete Mixtures", and the cement was the reference cement. The test results are shown in Table 1.
[0048] Table 1 Experimental results of C50 concrete
[0049] In the experiment of C50 concrete, by comparing the results of different embodiments and comparative examples, it can be clearly seen that the viscosity reducer of Example 3 performs best in multiple key performance indicators. Specifically, the viscosity of cement paste in Example 3 is significantly lower than that of other groups, indicating that it is most effective in reducing viscosity; at the same time, the high values of concrete slump and slump expansion further confirm its excellent fluidity and expansibility. In addition, Example 3 also shows the shortest time for emptying the inverted slump bucket, which is directly related to the construction performance of concrete. In terms of strength development, the compressive strength of Example 3 at 3 days, 7 days and 28 days is higher than that of other experimental groups, showing good early and long-term strength growth. Combining these results, the viscosity reducer of Example 3 not only provides convenience during the construction process, but also performs well in ensuring the long-term stability and durability of concrete structures, making it a preferred admixture in the production of high-performance concrete.
[0050] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A water-soluble star-comb polymer concrete viscosity reducer, characterized in that: The raw materials for preparing the water-soluble star-comb polymer concrete viscosity reducer include, by mass percentage, 20%-40% monomer, 0.05%-0.80% initiator PEO-Br3, 0.01%-0.20% catalyst, 0.05%-0.25% ligand, 0.001%-0.01% deactivator, and the balance is water.
2. The water-soluble star-comb polymer concrete viscosity reducer according to claim 1, characterized in that: The structure of the initiator PEO-Br3 is shown in formula (I): (I), n is 6 or 7.
3. The water-soluble star-comb polymer concrete viscosity reducer according to claim 1, characterized in that: The monomers include polyether methoxy polyethylene glycol methacrylate, maleic anhydride, and hydroxyethyl methacrylate phosphate.
4. The water-soluble star-comb polymer concrete viscosity reducer according to claim 3, characterized in that: The molar ratio of the polyether methoxy polyethylene glycol methacrylate, the maleic anhydride, and the hydroxyethyl methacrylate phosphate is 1:(0.5-4):(0.01-0.1).
5. The water-soluble star-comb polymer concrete viscosity reducer according to claim 3, characterized in that: The molecular weight of the polyether methoxy polyethylene glycol methacrylate is 1000-3000.
6. The water-soluble star-comb polymer concrete viscosity reducer according to claim 1, characterized in that: The catalyst is copper powder; And / or, the ligand is tris(2-dimethylaminoethyl)amine or tris(2-aminoethyl)amine; And / or, the deactivating agent is copper bromide.
7. The water-soluble star-comb polymer concrete viscosity reducer according to claim 1, characterized in that: The chemical structural formula of the water-soluble star-comb polymer concrete viscosity reducer is as shown in formula (II): (II), Among them, n, m, b, and y are all non-zero integers.
8. A method for preparing a water-soluble star-shaped and comb-shaped polymer concrete viscosity reducer, characterized in that: The following steps are involved: S1: Add polyether methoxy polyethylene glycol methacrylate, maleic anhydride, hydroxyethyl methacrylate phosphate and water into a reactor and stir to dissolve, then add catalyst copper and copper bromide, add ligand to react under constant temperature and vacuum conditions, then add initiator to initiate polymerization, and after the polymerization reaction occurs, seal the reactor; S2: After the reaction is carried out under closed conditions for a specified time, the reaction is stopped, the copper powder and the divalent copper complex in the reaction system are removed, and the reaction is concentrated by rotary evaporation. The concentrated solution is precipitated and then vacuum dried to obtain a star-shaped-comb-shaped polymer viscosity reducer.
9. The method for preparing the water-soluble star-comb polymer concrete viscosity reducer according to claim 8, characterized in that: The constant temperature is 20°C to 50°C.
10. The method for preparing the water-soluble star-comb polymer concrete viscosity reducer according to claim 8, characterized in that: The reaction time of adding the ligand reaction is 10min-30min; And / or, the time for reacting under closed conditions to a specified time is 60 min-240 min.
Citation Information
Patent Citations
Polycarboxylic acid superplasticizer having double-cross core configuration, and preparation method and application thereof
CN106749960A
Four-arm star-shaped block polycarboxylic acid super-plasticizer and preparation method and application thereof
CN110156944A
Preparation method of temperature / PH-responsive polycarboxylic acid
US20200223970A1
High-adaptability viscosity-reducing polycarboxylic acid water reducer, preparation method therefor and use thereof
US20210163355A1
